Kajian Empiris tentang Partisipasi dalam Pengambilan Keputusan - Rawis, Joulanda A. M. (Jurnal Aplikasi Manajemen, 2008)
This qualitative case study aimed to investigate theaters' participation in the school decision making. The data were collected through investigation, participatory observation, and documentation study. The study revealed that both the headmaster and teachers are involved in making decisions. The principal should offer the opportunity for teachers to get involved in decision making and teachers should actively take the opportunity.